Transgender athletes in sport: A conceptual decision-making framework enabled by athlete laboratory performance data - Hamilton, B. R. (University of Brighton, 2024)
The number of individuals attending transgender health services has increased in recent years in many countries, and the question of whether fair integration of transgender athletes into their affirmed gender sporting category is possible is becoming more prominent. This research aimed to develop a framework and supporting laboratory evidence to guide decision-making on the eligibility of transgender athletes to participate in elite sports. The first study established a conceptual framework to address how to integrate transgender women athletes into elite competition. By considering the physical demands and attributes needed for the sports of archery and shooting and comparing the current scientific literature on the effects of gender affirming hormone treatment, it was found to be justified that transgender women be permitted to compete in elite competition after two years of gender-affirming hormone treatment in archery and one year in shooting (Publication 1: Hamilton BR, Guppy FM, Barrett J, Seal L, Pitsiladis Y. Integrating transwomen athletes into elite competition: The case of elite archery and shooting. Eur J Sport Sci. 2021 Nov;21(11):1500-1509). Owing to laboratory closures during the pandemic making face-to-face data collection impossible, the student conducted a systematic review and meta-analysis that focused on the effects of exercise on bone mineral density (BMD) in healthy male subjects. This review revealed benefits of exercise on the femoral neck BMD (g = 0.21 [0.03, 0.40], Z = 2.23 p = 0.03) and not the lumbar spine BMD (g = 0.10 [-0.07, 0.26], Z = 1.15 p = 0.25) (Publication 2: Hamilton BR, Staines KA, Kelley GA, Kelley KS, Kohrt WM, Pitsiladis Y, Guppy FM. The Effects of Exercise on Bone Mineral Density in Men: A Systematic Review and Meta-Analysis of Randomised Controlled Trials. Calcified Tissue Int. 2022 Jan;110(1):41-56). In the third and main study of this PhD, laboratory measures of strength, power, and aerobic capacity of transgender athletes were compared with cisgender athletes. Specifically, 19 cisgender men (CM), 12 transgender men (TM), 23 transgender women (TW), and 21 cisgender women (CW) underwent a series of standard laboratory performance tests, including body composition, lung function, cardiopulmonary exercise testing, strength, and lower body power. Haemoglobin concenration ([Hb]) in capillary blood and testosterone and oestradiol in serum were also measured. In this cohort of athletes, TW has higher absolute strength (TW 40.7 ± 6.8 kg, CW 34.2 ± 3.7 kg, p = 0.01), lower modified FEV1:FVC ratio (TW 0.83 ± 0.07, CW 0.88 ± 0.04, p = 0.04), lower relative jump height (TW 0.7 ± 0.2 cm.kg-1; CW 1.0 ± 0.2 cm.kg-1, p < 0.001), and lower relative VO2max (TW 45.1 ± 13.3 ml.min-1.kg-1, CW 54.1 ± 6.0 ml.min-1.kg-1, p < 0.001) compared to CW athletes. TM have higher relative jump performance than TW (TM 0.9 ± 0.2 cm.kg-1, TW 0.7 ± 0.2 cm.kg-1, p = 0.01), lower absolute strength (TM 38.8 ± 7.5 kg, CM 45.7 ± 6.9 kg, p = 0.03) and absolute V?O2max (TM 3635 ± 644 ml.min-1, CM 4467 ± 641 ml.min-1 p = 0.002) than CM. These results should caution against precautionary bans and bans that are not based on sport-specific (or sport-relevant) research (Publication 3: Blair R. Hamilton, Andrew Brown, Stephanie Montagner-Moraes, Cristina Comeras-Chueca, Peter Bush, Fergus M. Guppy, Yannis P. Pitsiladis. The Strength, Power, and Aerobic Capacity of Transgender Athletes: A Cross-Sectional Study. BJSM - under review). Longitudinal transitioning studies of transgender athletes are urgently needed to confirm whether these findings are a direct result of gender-affirming hormone care.